REPRODUCTIVE ECOLOGY OF BIRDVILLE INDIGO, INDIGOFERA LINNAEI ALI. (FABACEAE) - Lakshminarayana, G.; Solomon Raju, A. J. (Journal of Institute of Science and Technology, 2017)
Indigofera linnaei, a low ground herb is an important species of herbaceous cover. It forms extensive mats of populations carpeting the soil. But, it is not known how it is able to increase its population size and spread into other areas. The knowledge of its reproductive ecology is important to understand its reproductive capabilities and evaluate its use in eco-restoration initiatives. The study aims to provide information on its reproductive ecology. I. linnaei flowers are papilionaceous, bisexual, monostylous, weakly protandrous, self-compatible, facultatively xenogamous and possess explosive pollination mechanism. High winds, high temperature and heavy rain trip the pollination mechanism and effect only selfing while bees and lycaenid butterflies trip pollination mechanism and affect both selfing and outcrossing. Thrips use the flower buds for breeding, emerge during anthesis and pollinate the flowers by feeding on pollen and nectar. The fruit is a pod which dehisces explosively to disperse seeds; long distance dispersal is facilitated by their irregular shape, oily nature, and carried away by wind and rain water. Therefore, ballistichory, anemochory and hydrochory are the functional modes of seed dispersal that enable the plant to invade and colonize especially open, sandy dry areas. The plant provides food for certain local insects and protects the soil cover with its clustered root system and spreading form of multi-stemmed branching pattern. Therefore, I. linnaei has the potential for use in the restoration of destroyed, degraded and damaged habitats. Journal of Institute of Science and Technology Volume 22, Issue 1, July 2017, Page: 84-93